(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study was aimed at determining the Gardnerella vaginalis in vaginosis women without miscarriage and vaginosis women with miscarriage. Also, another aim was the DNA sequencing was performed for phylogenetic tree analysis of the 16SrRNA gene in local Gardnerella vaginalis isolates in comparison with NCBIGenbank global Atopobium vaginae isolates and finally the submission of the present isolates in the NCBI-Genbank database. One hundred fifty (150) high vaginal swabs were collected from women with vaginosis (seventy-five samples were taken from married women with vaginosis without miscarriage and seventy-five samples from women with vaginosis with miscarriage) from Babylon City Hospital and private clinics. The age of the patient is 15–45 years. The sample was collected by disposable swabs; genomic DNA was extracted from these swabs. 16s rRNA gene detection by polymerase chain reaction technique. Gardnerella vaginalis was isolated on Columbia agar supplemented with 5% fresh blood with the addition of antibiotics. The study confirmed that 15 (20.00%) and 23 (30.66%) of Gardnerella vaginalis out of 150 swabs isolated from miscarriage and non-miscarriage vaginosis women, respectively, were isolated. According to molecular detection of the 16S rRNA gene, the study revealed that 67 (89.33%) and 72 (96.00%) of Gardnerella vaginalis out of 150 swabs obtained from miscarriage and non-miscarriage vaginosis women, respectively. BLAST analysis showed that the 16S rRNA gene shared more than 98-99% sequence compatibility with the sequences of Gardnerella vaginalis. Furthermore, the phylogenetic tree analysis of the 16S rRNA gene indicated that local Gardnerella vaginalis (NO. 1 and NO. 2) isolates shared higher homology with other Gardnerella vaginalis isolates available in the GenBank. The homology of the nucleotides was 98.50%, respectively.